2014
DOI: 10.1039/c4cp02860k
|View full text |Cite
|
Sign up to set email alerts
|

Low-melting mixtures based on choline ionic liquids

Abstract: In this article a strategy is proposed for the design of low toxic, room temperature liquid low-melting mixtures (LMMs) which are entirely composed of natural materials. From literature it is well known that, in general, deep eutectic solvents based on choline chloride and dicarboxylic acids are LMMs, but not liquids at room temperature, with one exception: a 1 : 1 molar mixture of malonic acid and choline chloride. Therefore, the starting point of this study was the decrease of the melting point of one of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Rengstl et al examined the thermal stability of ChCl-based DESs. 63 They found that the decomposition temperatures of ChCl-based DESs (269-280 ∘ C) are higher than those of HBDs and pure ILs. Thermal decomposition of DESs containing urea takes place in two steps, while a singular step mechanism is observed for DESs not containing urea.…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rengstl et al examined the thermal stability of ChCl-based DESs. 63 They found that the decomposition temperatures of ChCl-based DESs (269-280 ∘ C) are higher than those of HBDs and pure ILs. Thermal decomposition of DESs containing urea takes place in two steps, while a singular step mechanism is observed for DESs not containing urea.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Rengstl et al . examined the thermal stability of ChCl‐based DESs . They found that the decomposition temperatures of ChCl‐based DESs (269–280 °C) are higher than those of HBDs and pure ILs.…”
Section: Physicochemical Properties Of Dessmentioning
confidence: 99%
“…Moreover, the thermal stability of choline-based DES was studied by Rengstl et al [18] who reported that the decomposition temperature of these solvents is in the range of 269-290 ∘ C which is higher than those reported for ionic liquids [11]. …”
Section: Characterization Of Cholinementioning
confidence: 99%
“…However, there are some limitations to use these solvents because of the low solubility of organic compounds, high cost and long reaction time. In the recent years, scientists received a lot of attention towords the DES beacuse of its unique properties such as high polarity, low toxicity, nonvolatility, biodegradability, low cost, thermal stability and ready availability from bulk renewable resources . Due to such environmental benign properties of DES, it is used in many organic transformations .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, scientists received a lot of attention towords the DES beacuse of its unique properties such as high polarity, low toxicity, nonvolatility, biodegradability, low cost, thermal stability and ready availability from bulk renewable resources. [8][9][10][11] Due to such environmental benign properties of DES, it is used in many organic transformations. [12,13] DES is a mixture of hydrogen bond acceptors (HBAs) [14] such as choline chloride (ChCl), proline and hydrogen bond donors (HBDs) [15] such as tartaric acid, oxalic acid, urea, inorganic salts, alcohols and amines or carbohydrates.…”
Section: Introductionmentioning
confidence: 99%